1996
DOI: 10.1118/1.597661
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric verification of intensity‐modulated fields

Abstract: The optimization of intensity distributions and the delivery of intensity-modulated treatments with dynamic multi-leaf collimators (MLC) offer important improvements to three-dimensional conformal radiotherapy. In this study, a nine-beam intensity-modulated prostate plan was generated using the inverse radiotherapy technique. The resulting fluence profiles were converted into dynamic MLC leaf motions as functions of monitor units. The leaf motion pattern data were then transferred to the MLC control computer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
128
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(128 citation statements)
references
References 0 publications
0
128
0
Order By: Relevance
“…The LPO is corrected for in the MLC controller software using a table of corrections to the nominal leaf positions depending on the distance from the central axis 1 , 2 . The partial transmission of radiation through rounded leaf ends is modeled in Eclipse treatment planning system (TPS) (Varian Medical Systems) through increasing the distance between the opposite leafs, following work of Wang et al (3) The increase in the field size (measured at the isocenter) along the direction of leaf movement from the field size set by the ends of the leafs is referred to as the dosimetric leaf gap (DLG) (4) . The DLG is related to the radiation field offset (RFO), and numerically is twice as large (2) …”
Section: Introductionmentioning
confidence: 99%
“…The LPO is corrected for in the MLC controller software using a table of corrections to the nominal leaf positions depending on the distance from the central axis 1 , 2 . The partial transmission of radiation through rounded leaf ends is modeled in Eclipse treatment planning system (TPS) (Varian Medical Systems) through increasing the distance between the opposite leafs, following work of Wang et al (3) The increase in the field size (measured at the isocenter) along the direction of leaf movement from the field size set by the ends of the leafs is referred to as the dosimetric leaf gap (DLG) (4) . The DLG is related to the radiation field offset (RFO), and numerically is twice as large (2) …”
Section: Introductionmentioning
confidence: 99%
“…7). These are well known 24 to arise from the mechanical design of the MLC, but may be mitigated by the leaf sequencing algorithm used 25 . Since leaf sequencing is handled internally by our TPS, and given that the effects are not seen to pose a large perturbation on the delivery, tongue and groove effects are currently accepted as a minor delivery shortcoming.…”
Section: Resultsmentioning
confidence: 99%
“…The change in MLC gap width is referred to as the DLG or the radiation field offset. Vial et al (13) investigated the validity of several experimental techniques to determine the DLG and concluded that sliding gap MLC fields (16) should be used for measurement of the DLG.…”
Section: Introductionmentioning
confidence: 99%